Hubungan antara Indeks Massa Tubuh dengan Derajat Akne Vulgaris Pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - I Putu Madhava Wardhi Gosa; Suyasning Hastiko Indonesiani; Rima Kusuma Ningrum (Aesculapius Medical Journal, 2023)
Changes in the physiological condition of the body and various diseases can cause symptoms that manifest on the skin, one of those is acne vulgaris. Acne vulgaris is a condition of chronic inflammation of the sebaceous follicular unit one of it’s cause is Propionibactrium acnes infection and is very common in adolescence and can occur from pre-puberty to adulthood. Body Mass Index (BMI) is suspected to be one of the risk factors for acne vulgaris. This study aims to find the correlation between BMI and the incidence of acne vulgaris among Medical Faculty and Health Science Warmadewa University Students. The method of the study was analyzed observational which cross sectional approach. The BMI was measured by body weight (kg) devided by body height squared (m2) and incidence acne vulgaris by Global Acne Grading System. The samples were carried out on 120 students and the data were analyzed using SPSS 22. The results were showed as follows: there was a relationship between BMI and severity of acne vulgaris. The conclusion could be drawn that the relationship between BMI and acne vulgaris incidence was significant with p-value of 0,002 (p <0.05) and with Prevalence Risk (PR) of 1,19 (CI 95%, 1,003 – 1,413), thus students with underweight to normal BMI have risk of developing acne vulgaris with mild to moderate severity 1,19 times greater than students with overweight to obese BMI.. It could be recommended that students should be prevented from acne vulgaris by maintaining BMI in normal range . Key words: Acne Vulgaris, Body Mass Index (BMI), Pilosebaceous, Propionibacterium acnes.